The Implementation of Holistic Education in Muhammadiyahâs Madrasah Indonesia - Sutarman, Sutarman; Tjahjono, Heru Kurnianto; Hamami, Tasman (Dinamika Ilmu, 2017)
Holistic education is education which appreciates all of studentsâ potencies in learning process. This research is aimed at analyzing the implementation of holistic education in multilingual program of Madrasah Muâallimaat Muhammadiyah Yogyakarta. TheÂ  researchÂ  wasÂ  a descriptive-qualitativeÂ  approachÂ  withÂ  dataÂ  collectionÂ  techniques: in-depthÂ  interviews, participant observation, and documentation. The analysis of the data was by reduction, display, and provided conclusions. The result of the research shows that: (1) the implementation of holistic education toward the students of Multilingual program of Madrasah Muâallimaat was held through four quotients: spiritual quotient (SQ), emotional quotient (EQ), adversity quotient (AQ), and intellectual quotient (IQ) in which those quotients are integrated to madrasah and boarding. (2) Holistic education has impact on the transformation of the studentsâ character values, which are (1) intrinsic religiosity with deep faith-planted inside, (2) able to control emotion, self-motivated, care, and well-socialized, (3) the improvement of academic achievement, and (4) tough in facing problems, not easy of being hopeless, stressful, or frustrated.